Hubungan service quality dan keputusan memilih perguruan tinggi swasta : Scoping review - Purwantoro (Journals of Indonesian Multidisciplinary Research, 2024)
This study aims to identify and analyze the relationship between service quality and the decision to choose private universities (PTS) in Indonesia. Using a scoping review approach, this study reviewed various studies that used the SERVQUAL and SERVPERF models to measure service quality. The results showed that the dimensions of reliability and responsiveness had the most significant influence on students' decisions in choosing private universities. This study highlights the importance of private universities in improving the quality of their services to attract new students and retain existing students. The findings of this study are expected to provide valuable insights for private university managers in developing effective service quality improvement strategies, as well as contributing to the service quality literature in the context of higher education in Indonesia.